Motivation Analysis of Jennie’s Dream as Seen in Janet Quin-Harkin’s California Girl - Hastri Firharmawan (English Education and Literature Journal (E-Jou), 2022)
This study deals with Janet Quin-Harkin’s novel entitles “California Girl”. It was aimed to see the main character’s motivation in achieving her dream. It’s a qualitative study which employed psychological approaches. The primary data were in the forms of written expressions found in the narrations, dialogues, sentences and paragraphs in the novel showing the character’s behaviour and motivation in pursuing her dream. Data analysis applied procedures, namely data collection, data reduction, data serving, and drawing conclusion. To validate, data sources triangulation was used. The researcher read some related theories through books and articles. The study concluded that: First, Janet portrayed Jennie as a girl who was tall and skinny for her age with short mid-brown hair. She didn’t have a good physical outlook. She was introvert; and, therefore she had problem with social relationship. She was emotionally unstable and worried about losing her chance to make the Olympic team. Second, Jennie achieved her dream by trying to fulfil her fundamental needs for priorities. She ate enough food for her physical calories. After that, she fulfilled her psychological needs. She found love in Mark and never let him down. She also wanted to be accepted by her mother. Besides, swimming was her chosen sport to show that she was worth appreciating. Keywords: Analysis, motivation, dream